Determination of the design features of roadside air protection barriers of urban motorways using visual diagnostics and computational modelling - Vasiutynska, Kateryna; Arsirii, Vasyl; Smyk, Sergiy; Makovetska, Olena (Eastern-European Journal of Enterprise Technologies, 2025)
This study considers the aerodynamic characteristics of airflows on highways with protective roadside barriers. The task to optimize roadside barriers was addressed by analyzing airflow aerodynamic patterns using physical modeling and computational simulation. A flow structure visual diagnostics method (FSVD) was employed to analyze the kinematic features of airflow formation in the roadside barrier zone. It was established that the use of discrete-type barriers leads to the formation of stable air structures that enhance active flow mixing and dilution through external air entrainment. Each discrete element consists of a diffuser shield, expanding at an angle of 4° to the roadway axis, with a length equal to three lane widths. Additional elements in the form of parallel screens (confusors) are positioned between shields at an angle of 60° to the roadway axis. The combined approach, integrating FSVD and computational simulation in SOLIDWORKS Flow Simulation, provided a detailed representation of airflow behavior. It was determined that confusors between discrete shields generate an ejection effect, promoting external air entrainment and dilution within the roadway zone. This ensures unidirectional clean airflow and prevents exhaust gases from entering near-ground layers of residential areas. The applied computational model demonstrated the consistency and unidirectionality of dilution processes through ejection and dispersion via vertical flows. This enables better air circulation compared to conventional analogs, prevents stagnant zones, and reduces the impact of crosswinds and adverse atmospheric stability conditions. The devised structural solutions could be applied to design and optimize roadside barriers, particularly in residential areas